1985
DOI: 10.1161/01.cir.72.2.406
|View full text |Cite
|
Sign up to set email alerts
|

Survival after an experimental myocardial infarction: beneficial effects of long-term therapy with captopril.

Abstract: Although vasodilator therapy has been shown to improve functional capacity in patients with congestive heart failure, there is no evidence that such therapy can prolong survival. Coronary artery ligation in the rat was used to produce a wide range of myocardial infarct sizes and a resultant spectrum of left ventricular dysfunction. To determine the relationship between size of myocardial infarction and long-term survival and to test the hypothesis that long-term therapy with captopril could improve survival af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
294
1
10

Year Published

1989
1989
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 678 publications
(319 citation statements)
references
References 23 publications
(5 reference statements)
14
294
1
10
Order By: Relevance
“…These effects are not only mediated by circulating components, but also by paracrine effects of components of the cascade in several organs and tissues, including the heart, blood vessels, kidneys, and central nervous system. It has been described that infarcted rats treated long-term with captopril show hemodynamic preservation and improved survival (26). This classic study highlights the participation of the RAAS cascade in cardiac remodeling.…”
Section: The Cardiac Renin-angiotensin-aldosterone Systemmentioning
confidence: 71%
“…These effects are not only mediated by circulating components, but also by paracrine effects of components of the cascade in several organs and tissues, including the heart, blood vessels, kidneys, and central nervous system. It has been described that infarcted rats treated long-term with captopril show hemodynamic preservation and improved survival (26). This classic study highlights the participation of the RAAS cascade in cardiac remodeling.…”
Section: The Cardiac Renin-angiotensin-aldosterone Systemmentioning
confidence: 71%
“…13 The investigation conformed to the Guide for the Care and Use of Laboratory Animals published by the US National Institutes of Health. Adenoviral vector harboring the human kallistatin cDNA under the control of the cytomegalovirus enhancer/ promoter (Ad.HKS) or adenoviral vector alone (Ad.Null) (1 Â 10 10 plaque-forming units) was injected intramyocardially at six different sites along the border of infarcted area and noninfarcted area at 20 min after ligation.…”
Section: Materials and Methods MI Surgery In Rats And Adenoviral Vectmentioning
confidence: 99%
“…of other experimental models, where a decrease in mortality with the use of ACEIs after acute myocardial infarction was observed 26,27 . This difference could be explained by the duration of the study as those authors observed their animals for a period of one year but our follow-up lasted only three months.…”
Section: Referencesmentioning
confidence: 87%
“…Pfeffer et al 26 showed that the administration of captopril to rats reduces mortality in an observational period of one year after coronary artery occlusion only in animals with infarcts that occupied from 20% to 40% of the left ventricle (moderate infarct). Animals with small (<20% of the left ventricle) and large (>40% of the left ventricle) infarcts did not benefit from the treatment in regard to survival.…”
Section: Referencesmentioning
confidence: 99%